Chemical composition and medicinal significance of Fagonia cretica: a review. Issue 6 (18th March 2016) - Qureshi, Huma; Asif, Saira; Ahmed, Haroon; Al-Kahtani, Hassan A.; Hayat, Khizar
Abstract : Members of the family Zygophyllaceae are distributed in arid areas of the world and are traditionally used against various health insults ranging from skin lesions to lethal cancer. Fagonia cretica Linn. is a plant having novel compounds responsive in diseases that are still considered as incurable or are curable with serious side effects. Researchers, particularly of the Asian region elaborately studied the chemical composition and pharmacological activities of this plant. But further studies are still required to evaluate this plant in clinical trials in order to save humanity from synthetic chemical drugs yet disputed as 'friends or foe'. Abstract :